2010
DOI: 10.1016/j.bbamcr.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tumor suppressor PDCD4 by novel protein kinase C isoforms

Abstract: Transforming growth factor-beta1 (TGF-beta1) induces apoptosis in normal hepatocytes and hepatoma cells. PDCD4 is involved in TGF-beta1-induced apoptosis via the Smad pathway. The tumor promoter 12-O-tetradecanoylphorbor-13-acetate (TPA), a protein kinase C stimulator, inhibits TGF-beta1-induced apoptosis. However, the mechanisms of TPA action on PDCD4 expression remain to be elucidated. Therefore. the regulatory mechanism of PDCD4 expression by PKC was investigated. The treatment of the human hepatoma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…21 and 22). The degradation of the protein was stimulated through activation of the Akt-mTOR-S6K signaling pathway and the MAP kinase pathway (11,12,14). It was reported that the PDCD4 protein and mRNA levels were often not correlated in human tumors (16,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 and 22). The degradation of the protein was stimulated through activation of the Akt-mTOR-S6K signaling pathway and the MAP kinase pathway (11,12,14). It was reported that the PDCD4 protein and mRNA levels were often not correlated in human tumors (16,42).…”
Section: Discussionmentioning
confidence: 99%
“…Akt and ErK were also examined, because they function to control the PDCD4 levels by participating in the degradation of PDCD4 protein (11,12). Among them, only β-catenin expression was significantly correlated with PDCD4 expression (Fig.…”
Section: Pdcd4 Expression Is Correlated With β-Catenin Expression In mentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced PDCD4 Protein Stability and Increased PRMT5 Activity Converge to Increase Methylated PDCD4 during Nutrient Deprivation-Several kinases, including S6K, Akt, and the PKC ␦ and ⑀ isoforms, have been shown to phosphorylate PDCD4 S67, targeting it for polyubiquitination and proteasomal degradation (21)(22)(23). To test whether methylated PDCD4 is subject to proteasomal degradation, MCF7 cells coexpressing PDCD4 and PRMT5 were treated with and without MG132 to block proteasomal degradation under normal growth, during HBSS treatment, and during recovery.…”
Section: Methylated Pdcd4 Enhances the Interaction With Eif4a And Reqmentioning
confidence: 99%
“…Phosphorylation by several kinases, including S6K, Akt, and PKC ␦ and ⑀, at serine 67 targets PDCD4 for proteasomal degradation (21)(22)(23), and, because overactivation of the PI3K-mTOR 5 signaling cascade is a common occurrence in tumors (24,25), this mechanism is thought to be the cause of down-regulation of PDCD4 in many tumors. PDCD4 levels have also been reported to decrease during the mitotic phase of the cell cycle, concomitant with other changes in the status of translational machinery (26).…”
mentioning
confidence: 99%